Cytomegalovirus infection impairs immune responses and accentuates T-cell pool changes observed in mice with aging. - Luka Cicin-Sain; James D Brien; Jennifer L Uhrlaub; Anja Drabig; Thomas F Marandu; Janko Nikolich-Zugich (PLoS Pathogens, 2012)
Prominent immune alterations associated with aging include the loss of naïve T-cell numbers, diversity and function. While genetic contributors and mechanistic details in the aging process have been addressed in multiple studies, the role of environmental agents in immune aging remains incompletely understood. From the standpoint of environmental infectious agents, latent cytomegalovirus (CMV) infection has been associated with an immune risk profile in the elderly humans, yet the cause-effect relationship of this association remains unclear. Here we present direct experimental evidence that mouse CMV (MCMV) infection results in select T-cell subset changes associated with immune aging, namely the increase of relative and absolute counts of CD8 T-cells in the blood, with a decreased representation of the naïve and the increased representation of the effector memory blood CD8 T-cells. Moreover, MCMV infection resulted in significantly weaker CD8 responses to superinfection with Influenza, Human Herpes Virus I or West-Nile-Virus, even 16 months following MCMV infection. These irreversible losses in T-cell function could not be observed in uninfected or in vaccinia virus-infected controls and were not due to the immune-evasive action of MCMV genes. Rather, the CD8 activation in draining lymph nodes upon viral challenge was decreased in MCMV infected mice and the immune response correlated directly to the frequency of the naïve and inversely to that of the effector cells in the blood CD8 pool. Therefore, latent MCMV infection resulted in pronounced changes of the T-cell compartment consistent with impaired naïve T-cell function.